De billige bøgers indtog i dansk boghandel 1908-1918 - Ilsøe, Harald (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
In the autumn of 1908, publisher John Martin embarked on his series of translated literary works at 50 øre apiece, the so-called “half-krone editions”, soon supplemented by the slightly weightier “standard editions” at one krone apiece. One important factor for these cheap editions was the large print-run of around 10,000 copies, not seldom rising to 20,000 or more. The established book trade initially stood aloof and criticised Martin’s sales methods, but their success could not be denied, and little by little other publishers followed suit with book series at similar prices. Finally, the largest and dominant publisher, Gyldendal, gave in to the cheap book trend, when in 1916-17, following Martin’s example, it issued both a half-krone and a one-krone series of translated novels, which rapidly achieved impressions of 25-34,000 copies. Other cheap books in large print-runs were sold outside the regular bookshops by direct sale to customers through tempting advertisements in newspapers and magazines. This method succeeded not least for Heinrich Matthiasen and his “Kunstforlaget Danmark” company, which, like Martin’s house, started up in 1908 and is thought to have culminated in 1913 with a production of 2,545,000 books, including a five-volume edition of Ingemann in 150,000 copies. As did certain other publishers, Matthiasen exploited the fact that large batches of books could be bound very cheaply, and he made most of his profit from selling ready-bound books. Several of the cheap book series named in the article are recorded under their series name in the Danish Book List, whereas it is hard to get a clear idea of “Kunstforlaget Danmark’s” production. For this reason, a concluding appendix lists these books up to 1915/16, with the exception of books with fewer than 160 pages.